2017
DOI: 10.1016/j.ijfoodmicro.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Penicillia associated with Italian grana cheese

Abstract: The present work aimed to contribute information on the mycobiota associated with ripening grana cheese, with focus on the genus Penicillium as potential mycotoxin producers. Eighteen wheels of grana cheese, aged in different storehouses situated in Northern Italy, were sampled to isolate associated fungi. Penicillium spp. were commonly dominant; morphological observation and gene sequencing were applied to identify Penicillium at species level. P. crustosum and P. solitum were the dominant species. Citrinin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Fröhlich-Wyder et al (2013) determined that L. buchneri and L. parabuchneri isolated from cheese do not affect cheese quality or its flavours, but improve its chemical composition and eye formation by enhancing gas production. Several authors have reported the presence of OTA in different types of cheesesblue cheese, hard cheese, traditional Italian cheese, Gorgonzola, Roquefort and white cheeses (Dall'Asta et al 2008;Pattono et al 2013;Benkerroum 2016;Decontardi et al 2017). Others associate P. nordicum with the production of OTA in cheeses (Larsen et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Fröhlich-Wyder et al (2013) determined that L. buchneri and L. parabuchneri isolated from cheese do not affect cheese quality or its flavours, but improve its chemical composition and eye formation by enhancing gas production. Several authors have reported the presence of OTA in different types of cheesesblue cheese, hard cheese, traditional Italian cheese, Gorgonzola, Roquefort and white cheeses (Dall'Asta et al 2008;Pattono et al 2013;Benkerroum 2016;Decontardi et al 2017). Others associate P. nordicum with the production of OTA in cheeses (Larsen et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of toxigenic fungi on grana cheese, during ripening and storage [5,10,20] is a matter of concern for manufacturers and consumers, because of the possible production of different mycotoxins. There is a complete lack of regulation for mycotoxins (with the exception of aflatoxin M 1…”
Section: Discussionmentioning
confidence: 99%
“…is reported as the dominant fungal genus growing on cheese [4]. Information about penicillia growing on grana cheese during ripening has been reported by Decontardi et al [10,12]. In particular, P. crustosum and P. solitum were the dominant species isolated, but other mycotoxin producing fungi identified were A. flavus and P. verrucosum.…”
Section: Of 14mentioning
confidence: 91%
See 2 more Smart Citations